Epidermal cyst causing facial asymmetry - Pereira-Santos, Darklilson; DeMelo, Willian Morais [UNESP]; Brêda Jr., Marcus Antônio; Sonoda, Celso Koogi [UNESP]; Hochuli-Vieira, Eduardo [UNESP] (Wolters Kluwer, 2013)
Epidermoid cysts are rare benign tumors that are derived from the development of abnormally situated ectodermal tissue and are often an incidental finding. They are usually diagnosed between 15 and 50 years of age, with both sexes equally affected. In epidermoid cyst management, complete excision is the therapy of choice. The authors reported a case of a 24-year-old man with an epidermoid cyst located on the left side of the face, on the region of mandibular body, which was treated by complete surgical excision. The patient has been followed up for 2 years without signs of recurrence. Copyright © 2013 by Mutaz B. Habal, MD.
Keywords: Benign tumors; Epidermoid cyst; Face; Recurrence; Surgical management